PERLINDUNGAN HUKUM BAGI PEMEGANG HAK DESAIN INDUSTRI SEPATU TERHADAP IMITASI (Studi Perbandingan dengan Amerika Serikat) - Muhammad Faizal Akbar Laksmana (Legal Standing : Jurnal Ilmu Hukum, 2021)
The development of the shoe industry in Indonesia today raises new problems where the similarity of shoe designs between several brands is a new problem that arises. The shoe industry design rights holders which should be highly protected have not fully received strong legal protection and there are no regulations that discuss in detail about design imitation. This writing uses a comparative method, namely the author compares with the United States that has protected industrial design rights holders since 1989 and has proven successful in protecting industrial design rights holders, therefore this comparison is important so that regulations on industrial design rights in Indonesia can benefit rights holders.